Central African Economic and Monetary Community (CEMAC) : 2013 Staff Report on Common Policies for Member Countries. (IMF Staff Country Reports; Country Report ;, 2013)
This paper focuses on common policies for member countries of Central African Economic and Monetary Community (CEMAC). It highlights that the fiscal stance should be more cautious in some countries where policy buffers are insufficient to withstand shocks. The recent easing of monetary policy has been appropriate given the positive inflation outlook. Reserves coverage remains adequate and the real effective exchange rate is broadly in line with fundamentals but the issue of only partial repatriation of foreign exchange reserves by some member states needs be resolved. The fiscal surveillance framework should be revised to limit pro-cyclicality and better ensure long-term fiscal sustainability of oil-rich countries.